EVALUASI KERENTANAN SEISMIK PADA BANGUNAN DI KABUPATEN LINGGA MENGGUNAKAN RAPID VISUAL SCREENING (RVS) - Dhio Pratama, Aldrin; Reni Suryanita; Kurniawandy, Alex (Jurnal Infrastruktur, 2026)
Earthquakes are natural disasters that occur due to sudden shifts in the earth's crust. Indonesia is prone to earthquakes because it lies at the meeting point of three major tectonic plates, namely the Indo-Australian, Eurasian, and Pacific plates. One of the areas studied is Lingga Regency, which is located on the coast of the South China Sea and has a low earthquake rate. These two conditions can cause problems if the structural resistance, quality, and impact of damage caused by seawater salt are not taken into account. The purpose of this study is to evaluate earthquake vulnerability in areas with low seismic activity, concrete quality, and damage to building structures. The methods used for evaluation were Rapid Visual Screening (RVS), Non-Destructive Testing (NDT), and visual inspection. The results showed that the final RVS score at the moderate level indicated vulnerability to earthquakes in buildings B and D. Concrete quality testing on the tie beam elements of building A and the column and tie beam elements of building K did not meet the minimum requirement of 17 MPa based on the limits of SNI 2847:2019, and through visual inspection, only buildings A and K were found to have damage to the slabs. beam and slabs. The results of this evaluation can be used as a basis for implementing pre-disaster mitigation measures on the buildings, and these steps can also serve as a reference for disaster mitigation policies at the Lingga regency level.